Asian and Pacific American education : learning, socialization, and identity - Park, Clara C., 1944-; Endo, Russell; Goodwin, A. Lin (Emerald Publishing Limited : Information Age Publishing, 2006)
This research anthology is the third volume in a series sponsored by the Special Interest Group -Research on the Education of Asian and Pacific Americans (SIG-REAPA) of the American Educational Research Association and National Association for Asian and Pacific American Education. This series explores and explains the lived experiences of Asian and Pacific Americans as they attend schools, build communities and claim their place in U.S. society, and blends the work of well-established Asian American scholars with the voices of emerging researchers and examines in close detail important issues in the Asian/Pacific American community. Scholars and educational practitioners will find this book to be an invaluable and enlightening resource.
Keywords: Asian Americans -- Education -- Case studies.; Pacific Islander Americans -- Education -- Case studies.; Asian Americans -- Socialization -- Case studies.; Pacific Islander Americans -- Socialization -- Case studies.; Asian Americans -- Ethnic identity -- Case studies.; Pacific Islander Americans -- Ethnic identity -- Case studies.; elektronické knihy; Case studies.; Social Science -- Cultural & Ethnic Studies -- American -- Asian American & Pacific Islander Studies.; Educational strategies and policy: inclusion.; Ethnic studies.; United States of America, USA.; Relating to Asian American, Pacific Islander American people.; electronic books